Facing the fear: a narrative review on the potential of pressure training in music - de Bie, Nicky; Hill, Yannick; Pijpers, J. R. (Rob); Oudejans, Raôul R. D. (Frontiers in Psychology, 2024)
Music performance anxiety (MPA) is one of the most reported psychological problems among musicians, posing a significant threat to the optimal performance, health, and psychological wellbeing of musicians. Most research on MPA treatment has focused on reducing symptoms of performance anxiety, but complete “cures” are uncommon. A promising addition or alternative that may help musicians enhance their performance under pressure, despite their anxiety, is pressure training (PT). In other high-pressure domains, such as sports and police work, pressure training has been proven effective in reducing choking and enhancing performance quality under pressure. Therefore, the aim of this narrative review is to explore the potential of pressure training in music settings. Specifically, we first provide a theoretical overview of current models explaining performance declines due to anxiety. Second, we discuss the current state of research on the effectiveness and application of pressure training in sports and police work as well as recent developments in pressure training interventions for music settings. While there is a limited number of studies investigating the effectiveness of pressure training on musicians' performance quality, research focusing on musicians' experiences has shown that pressure training can be particularly beneficial for enhancing performance skills, preparing for performances, and managing performance anxiety. Based on the reviewed literature, the final section points out suggestions for future research as well as recommendations for musicians, teachers, and music institutions for practical applications.